Současný pohled na koenzym Q - Rauchová, Hana; Vokurková, Martina (Chemické listy, 2009)
Coenzyme Q (CoQ), a lipophilic substituted benzoquinone present in all cells. Besides its fundamental role of an electron carrier associated with energy production in the respiratory chain, CoQ has two other functions in mitochondria. It is an essential factor in activation of protein uncoupling and it controls permeability of transition pores. Moreover, it participates in extramitochondrial electron transport in plasma membranes and lysosomes, controls physicochemical properties of membranes, and is the only endogenous lipid antioxidant. Its pro-oxidant role consists in generating the major superoxide radical/H2O2 secondmessenger system. Biosynthesis of CoQ proceeds in every cell, small amounts of CoQ can be obtained from diet. CoQ is also available as a dietary supplement. It shows minimal toxicity, excellent tolerance, and no significant side effects. Its beneficial effects are largely attributed to its essential role in cellular bioenergetics and antioxidant properties. Supplementation of CoQ can improve conditions of a wide range of pathological states. Some forms of mitochondrial CoQ deficiency respond well to its oral administration. Recent meta-analysis of tests for hypertension is also promising. This review summarizes the current knowledge of the therapeutic efficacy of CoQ in various diseases.
Keywords: financování organizované; klinické zkoušky jako téma; ubichinon; Clinical Trials as Topic; Antioxidants; lékové interakce; Mitochondria; Drug Interactions; Drug-Related Side Effects and Adverse Reactions; Dietary Supplements; energetický metabolismus; lidé; Energy Metabolism; potravní doplňky; mitochondrie; Financing, Organized; Humans; oxidace-redukce; nežádoucí účinky léčiv; Oxidation-Reduction; medicína založená na důkazech; antioxidancia; Oxidants; Evidence-Based Medicine; oxidancia; Ubiquinone